2018
DOI: 10.14569/ijacsa.2018.090623
|View full text |Cite
|
Sign up to set email alerts
|

An Effective Virtual Reality based Remedy for Acrophobia

Abstract: Virtual reality (VR) Exposure Therapy with sophisticated technology has been used in the Psychological treatment. The goal is to design a virtual environment using HCI (HMD) device with an interactive and immersive realistic 3D graphic scenes for exposure therapy of acrophobia that allows patient to sense height and gets used to the fearful feelings .The degree of fear is then used to evaluate the effectiveness of the system before and after therapy with the help of comparison. One may feel a little uneasy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 9 publications
1
6
0
2
Order By: Relevance
“…This suggests that the VRET module works to alleviate acrophobia symptoms. The findings of this study are consistent with those of Abdullah and Shaikh (2018), who found that an 8-session Virtual Reality Exposure treatment was successful in lowering anxiety in 10 people suffering from acrophobia. The same study discovered that VRE therapy outperformed in vivo exposure.…”
Section: Discussionsupporting
confidence: 91%
“…This suggests that the VRET module works to alleviate acrophobia symptoms. The findings of this study are consistent with those of Abdullah and Shaikh (2018), who found that an 8-session Virtual Reality Exposure treatment was successful in lowering anxiety in 10 people suffering from acrophobia. The same study discovered that VRE therapy outperformed in vivo exposure.…”
Section: Discussionsupporting
confidence: 91%
“…The classification in [20] is too concise to fully include the existing SGPT. On the other hand, the classification in [25] is too detailed, which increases the complexity of system development. Therefore, compared to the classification in literature [20] and [25], our classification is more neutral and reduces the complexity of game development while ensuring that all phobias are included as far as possible.…”
Section: Serious Games Classification Based On Different Types Of Phobiamentioning
confidence: 99%
“…VR users get a fear of virtual heights (Clark, 2013), get scared to death of virtual spiders (Tardif, 2019), and experience worries during social interactions (Diemer, 2015). Multiple research publications demonstrate that virtual reality is a great way of manipulation of psycho-emotional state of users (Abdullah, 2018), especially when gamification is applied (Hvass, 2018).…”
Section: High Degree Of Realismmentioning
confidence: 99%